Factors influencing transfer of training among academics in Public Universities in Malaysia - Zulkifly, Nurul Afiqah; Ismail, Ismi Arif; Asimiran, Soaib; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2021)
Universities have increasingly begun to emphasise the importance of leadership development program for academic leaders as they are the key players of the institutions. However, training programs are often not properly evaluated to determine return of investment. Transfer of training needs to be evaluated in order to justify the return of investment spent by stakeholders. Therefore, this paper aims to determine the influence of trainee characteristic (learner readiness and motivation to transfer), training design (perceived content validity and transfer design) and work environment factors (peer support and supervisor support) on transfer of training involving 120 academics who are currently working at two public universities in Malaysia. This paper adopts the Baldwin and Ford’s (1988) transfer process model to investigate the relationships between the predictors and transfer of training. The respondents of this study participated in a one-day leadership development program, one and a half months prior to the data collection process. The findings of this study indicates that learner readiness, perceived content validity and peer support significantly influence transfer of training among the academics.